Transition Engineering co-design sprint: oil company business model - Boulton, Jack; Krumdieck, Susan (Frontiers in Sustainability, 2025)
International oil companies (IOCs) face competing pressures to reduce production to meet climate targets while delivering expected shareholder value. These competing pressures create a dissonance surrounding the future business strategy of IOCs. The Systems Transition Engineering approach brings experts together to work through an Interdisciplinary Transition Invention, Management and Engineering (InTIME) Design Sprint, to generate novel concepts for business options that relieve competing pressures in complex and unsustainable systems. This article details a case study of an InTIME Design Sprint conducted with oil industry experts involving a series of investigative workshops. The aim of the sprint is to generate foresight for IOC business pivot opportunities that resolve the dissonance surrounding IOC futures in a climate-safe world. A pivot opportunity represents a profitable business strategy within the bounds of what is feasible and socially acceptable. A theoretical oil company was used to test out hypothetical business scenarios throughout the steps of the sprint. The design sprint was successful in moving the oil industry experts beyond the dissonance and facilitating the foresight of viable and climate-safe business pivot opportunities for an IOC. This result represents a breakthrough that was previously considered unthinkable by the sprint participants. This work contributes a novel use case of the InTIME Design Sprint to an upstream energy system and introduces novel applications of tools to navigate cognitive dissonance and complexity within InTIME Design Sprints.